Informática para Terceira Idade - Socialização e Inclusão Digital do Público Idoso - Carvalho, Vitória Dutra de; Reis, Luis Paulo de Souza; Silva, Maria Fernanda Lima da; Indalécio, Caio Lucas; Rodrigues, Kamila Rios da Hora; Valem, Lucas Pascotti (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16389, 2025)
This paper describes the structure and methodology of a digital literacy program for the elderly, conceived and implemented in the first semester of 2025, with plans for future editions. This university outreach project has yielded significant results for the surrounding community. Through weekly in-person classes, with the help of somewhat individualized monitoring, seniors are taught and encouraged to test and expand their digital skills, increasing their knowledge of social networks. Classes at our university demonstrated the relevance of digital literacy programs for seniors. This work presents accounts of the course’s structure and implementation, as well as accounts from some senior students and tutors.